Field experimental study on pullout forces of rice seedlings and barnyard grasses for mechanical weed control in paddy field - Jinwu, Wang; Guixiang, Tao; Yongjun, Liu; Zhenwei, Pan; Chunfeng, Zhang (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: Pullout forces of rice seedling and barnyard grass were tested by universal testing machine controlled by WDW-5 type microcomputer to obtain the pullout forces of rice seedling and barnyard grass. The measured pullout force was used to improve the weeding rate and reduce the rice seedling damage rate caused by mechanical weeding device. According to the measured continuous curve of pullout forces of rice seeding and barnyard grasses in weeding period, the best range of force required to pull out barnyard grasses from soil with no injury and damage to rice seedlings was discussed. Reasons for the difference in the pulling force were analyzed. Results show that, with the increment of the number of single cell rice seedlings the pullout force increases. The pullout forces of single cell rice seedlings and barnyard grasses at first increased slowly reaching the maximum value followed by rapid drop and finally it remained steady. The minimum pullout forces recorded during rice seedlings at the first and the second weeding periods were 2.57 N and 9.70 N, respectively, while the minimum forces during the first and second weeding periods were recorded as 1.24 N and 7.51 N, respectively, for barnyard grasses. The results show that the pullout forces of weeding to rice seedlings and barnyard grasses should be within 1.24 N to 2.57 N and 7.51 N to 9.70 N respectively in the first and second weeding periods. Keywords: paddy field, mechanical weed control, pullout force, rice seedlings, barnyard grasses, field test DOI: 10.3965/j.ijabe.20140706.001 Citation: Wang J W, Tao G X, Liu Y J, Pan Z W, Zhang C F. Field experimental study on pullout forces of rice seedlings and barnyard grasses for mechanical weed control in paddy field. Int J Agric & Biol Eng, 2014; 7(6): 1－7.